Applications of training in social skills: analysis of national production / Aplicações do treinamento em habilidades sociais: análise da produção nacional - Sheila Giardini Murta (Psicologia: Reflexão e Crítica, 2005)
Social skills are recognized as protection factor in the human development course. As a result, programs targeted at development of social skills have been done to promote mental health. This article describes programs of social skills training with Brazilian samples for primary, secondary and tertiary prevention. Participants, design, evaluation instruments, intervention techniques and results were focused. Search on journals, LILACS base data and books written by research groups identified 17 intervention programs. The literature showed the predominance of programs in group, in clinical and educational contexts, with pre-experimental designs, and use of cognitive-behavioral techniques. Results found are promising toward improvement in social performance. Suggestions to planning of future interventions are presented.